Legal Protection of Patients’ Confidentiality in the Era of Mandatory Electronic Medical Records - Hendrata, Winona May; Karim, Asma (Fakultas Hukum Universitas Widya Mataram, 2025)
Electronic medical records (EMR) is the result of technology and information advancement in healthcare. However, the implementation of EMR has not been optimal, thus doubts about patient’s data security inevitably rise. The method used in this research is statute approach. Implementation of EMR is obligated through the enactment of Indonesian Health Ministerial Regulation. The obligation to guard professional secret is regulated in legal enactment, as well as within health professionals code of ethics. EMR system with adequate requirement is crucial in order to guarantee the security of the data contained. The EMR system requirement has been regulated within the Health Ministerial Regulation, however more detailed technical explanation is still needed. Moreover, secret disclosure is a crime under Indonesian Penal Code, and unlawfully accessing information system is punishable by law. Legal protection of patient confidentiality are expected to maintain the trust of patients toward healthcare facilities that has utilized EMR. Keywords: electronic medical records; health law; patient confidentiality